The Impact Of Artificial Intelligence Tools On Vocabulary Learning Of Students At The Islamic University Of Lebanon - Jana Mohammad Saab; Ali Wissam Abu Melhem (The Journal of Studies in Language, Culture and Society)
Artificial Intelligence transcends the digital world to reach the field of education, specifically the English language. This study attempts to investigate the effect of artificial intelligence tools on vocabulary learning of university students at the Islamic University of Lebanon. There is a lack of having solid academic vocabulary words that help in developing students’ reading and writing skills. Considering this matter, this study endeavors to show the important need to utilize AI tools in vocabulary teaching/learning, for its positive influence on this skill at the university. This study is a mixed method research that involves collecting data from pre-test, post-test, and interviews. The sample comprises two sections of university students at one of the faculties of 80 students. One section was assigned as the experimental group (40 students), and the other section was assigned as the control group (40 students). All data was collected, analyzed, and portrayed in the form of inferential statistics using the SPSS program. Data analysis showed that the research hypotheses were proven and the research questions were answered. Indeed, the research results revealed that integrating AI tools in vocabulary learning supported university students, who are learners of English as a Foreign Language, ace academic vocabulary words that can be used in their writing, understand and make use of newly learned words, and enriched their vocabulary bank.